SOUND SOURCE LOCATION METHOD (Perner's Contacts, 2011)
This paper deals with received acoustic signals on microphone array. In this paper the localization system based on a speaker speech processing and extraction of sibilant sequence is suggested. It is shown, that this method leads to good position estimation accuracy in indoor systems.
Keywords: localization; sound; microphone array